Characterizing the Mesencephalon Using Susceptibility-Weighted Imaging - Manova, E.S.; Habib, C.A.; Boikov, A.S.; Ayaz, M.; Khan, A.; Kirsch, W.M.; Kido, D.K.; Haacke, E.M. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: The mesencephalon is involved in a number of human neurodegenerative disorders and has been typically imaged with T1-, T2- and T2*-weighted methods. Our aim was to collect high-contrast susceptibility-weighted imaging (SWI) data to differentiate among and within the basic mesencephalic structures: namely, the red nucleus, substantia nigra, and crus cerebri.MATERIALS AND METHODS: High-resolution SWI, 3D T1-weighted, and T2-weighted data were collected to study contrast in the mesencephalon at 1.5T and 4T. Contrast between structures was calculated for SWI high-pass (HP)-filtered-phase, T1 gradient-echo, and spin-echo T2-weighted data.RESULTS: SWI HP-filtered-phase data revealed similar contrast for the red nucleus and substantia nigra when compared with T2-weighted imaging. However, SWI was able to show structures within the red nucleus, substantia nigra, and medial geniculate body that were invisible on T2-weighted imaging. T1-weighted imaging, on the other hand, did not reveal measurable contrast for any of the structures of interest. SWI HP-filtered-phase data at 4T agreed well with india ink−stained cadaver brain studies, which appear to correlate with capillary density.CONCLUSIONS: With SWI, it is possible to create better anatomic images of the mesencephalon, with improved contrast compared with conventional T1- or T2-weighted sequences.